Nurse following hospital robot with special wheels and sensor intergration - Bukhari, Ilias; Ramachandran, Nagarajan, Prof.; Azrul, Ahmad; Sulaiman, Bakri; Awang Sabri, Awang Omar; Muhammad Asyraf, Abdul Rahman (Universiti Sains Islam Malaysia (USIM), 2012)
Exposition on Islamic Innovation 2011 (i-NOVA 2011) was organized by Universiti Sains Islam Malaysia (USIM) and Ministry of Higher Education (MOHE), 14th - 16th October 2011 at Stadium Tertutup Nilai, Negeri Sembilan, Malaysia.